AN APPROXIMATE FORMULA FOR THE STRESS INTENSITY FACTOR FOR THE PRESSURIZED STAR CRACK - CLEMENTS, D. L.; WIDANA, N. (Jurnal Matematika; Vol. 1, No. 1 April 2007DO - 10.24843/JMAT.2007.v01.i01.p06)
An elementary approximate formula for the stress intensity factor for the pressurized star crack is estab-lished. The formula is sufficiently accurate to be used in practical applications in place of the more complex formulas derived by Westmann [1] and Williams [2]. © 2003 Elsevier Science Ltd. All rights reserved.
Keywords: stress intensity factors, Cracks, Inequalities, Fracture mechanics.